Airworthiness analysis of low earth orbit satellite communication technology for UAV application - Yaoyu HE; Chao ZHANG (Dianxin kexue)
With the rapid development of unmanned aerial vehicle (UAV) and low earth orbit (LEO) satellite technology, the integrated network consisted of the space, air, ground and sea has promoted the wide development of Internet of remote things (IoRT) on the UAV platform.Confronting the application demand of UAV with LEO satellite, the corresponding flight safety of UAV needs to be considered firstly, and the airworthiness of UAV has become the top priority of the technical application.The significance of the airworthiness of the UAV system was introduced and the technology of LEO satellite with UAV was summarized.Moreover, the related airworthiness programs of UAV equipped with LEO communications system were proposed.Meanwhile, based on the comprehensive analysis of UAV oriented LEO satellite technology, the means of compliance (MOC) on the airworthiness theory has been carried out.